Long-term Results of Carpal Tunnel Release Using Agee’s Single Portal Endoscopic Technique - Pataradool, MD, Kawee; SH, MD, Tan; Yong, MD, FC; Teoh, MD, LC (Journal of Southeast Asian Orthopaedics, 2022)
Purpose: Open carpal tunnel release (OCTR) is the standard treatment after failed conservative management for carpal tunnel syndrome. Endoscopic carpal tunnel release (ECTR) has been developed and has been used increasingly over the last few years. According to several studies, ECTR results in a more rapid return to work and less scar tenderness than OCTR. Most studies have had short-term follow-ups and it is important to assess its long-term results. This study presents long-term results of ECTR by using a standard questionnaire. Methods: There were 76 patients (94 hands) who underwent endoscopic carpal tunnel release (ECTR), using Agee’s single portal technique since July 1992 till October 1994. The Boston questionnaire was used to evaluate the long term results and patient satisfaction of this procedure, 28 patients (36 hands) responded with a mean age of 55 years at the time of operation and the mean follow-up period was 120 months. No complications developed in any patient. The Boston questionnaire is a self-administered questionnaire for the assessment of the severity of symptoms and functional status in patients who have carpal tunnel syndrome. There are 11 questions for symptom severity scoring, and 8 questions for functional severity scoring. The score varies from 1 (no problem) to 5 (very severe problem). The mean scores and standard deviations for symptom severity and functional status scores were recorded and classified into a range, with a score of 1-2 representing satisfactory, 2-3 as acceptable, 3-4 as fair, and 4-5 as unacceptable. Results: Mean symptom severity scores were 1.41 and mean functional status scores were 1.32. 96.43 % had no scar discomfort, and only 3.57 % had mild symptoms. All patients were satisfied with the results of the operation. Conclusion: The subjective assessment of the long-term results of ECTR in our patients, using the Boston questionnaire was rated as satisfactory, and the results were comparable, if not better, than prior studies, which used the same questionnaire to assess conventional open carpal tunnel release.